Compensation Process for People Who Are Victims of Trading with Binary Option Systems - Muhammad Fajri Juliardhi (Proceedings Series on Social Sciences & Humanities, 2023)
Binary Option is the activity of determining the price movement of an asset within a certain period of time as chosen by the trader in the online trading terminal. assets that can be represented by company shares, stock indices, currency pairs (exchange rates from one currency to another), the price of goods in exchange for commodities, commodity options, and so on. This study aims to determine the legality and settlement process of compensation. loss to victims of binary options trading cases. The method used by the author in this research is using the normative juridical method. The normative juridical research is carried out by means of a literature study by basing its analysis on the applicable laws and regulations and is relevant to the legal issues that are the focus of the research, researching library materials or secondary materials with a statutory approach. invitation (Statute Approach) by reviewing all laws and regulations related to the problems (legal issues) being faced based on the research results obtained Legally, the legality in the Binary Option system does not meet the legal criteria because from a legal perspective binary options are prohibited by Bappebti because it is an activity prohibited by the PBK (Commodity Futures Trading) Law Article 1 number 8 of UU No. 10 of 2011 concerning Changes Based on UU No. 32 of 1997. Forms of legal protection for victims of losses suffered as a result of these crimes, there are three ways to take the right of restitution, victims can request restitution rights to LPSK, victims can claim compensation under Article 1365 of the Civil Code for unlawful acts and the rights of victims can be obtained by combining cases in court in accordance with article 98 of the Criminal Procedure Code.